Traditional uses of plants in Gokwe South District, Zimbabwe: construction material, tools, crafts, fuel wood, religious ceremonies and leafy vegetables - Mapaya, Ruvimbo Jessy; Shopo, Bridgett; Maroyi, Alfred (Ethnobotany Research and Applications, 2022)
Background: Most people who reside in rural areas have over the years benefited from the utilization of forest products obtained from forests and surrounding woodlands. Both timber and non-timber forest products are important in livelihood maintenance, provision of security, reduction of poverty and malnutrition and help generate income. The aim of the study is to evaluate and document plants that are traditionally used by community in Gokwe South District, Zimbabwe and to assess their contribution to the livelihood and sustenance of the community. Methods: Ethnobotanical data was collected from February 2022 till March 2022 through semi-structured interviews and data analysed through quantitative indices such as use value (UV) and relative frequency of citation (RFC). Field surveys were made to collect voucher specimens, which were identified, authenticated and deposited at the National Herbarium, Zimbabwe. Results: A total of 89 plant species belonging to 81 genera and 44 families are traditionally used in Gokwe South District. The Fabaceae family is the highest plant species (15 species) followed by Anacardiaceae and Euphorbiaceae (five species each). Seven use categories were identified with the food category recording the highest number of plant species used (48 species) followed by tools and handicraft (29 species). Conclusions: The study showed that the traditional use of plant is still a common practice in the district. The great diversity of plants gives the need for their conservation and sustainable use to be established and monitored. Keywords: Plant diversity, use patterns, traditional uses of plants, Gokwe South District